Solanidine isolation from Solanum tuberosum by centrifugal partition chromatography. Issue 14 (15th July 2013) - Attoumbré, Jacques; Giordanengo, Philippe; Baltora‐Rosset, Sylvie
<x xml:space="preserve">Abstract</x> The aim of this investigation was the preparative isolation of solanidine (aglycone of the two main potato glycoalkaloids: α‐chaconine and α‐solanine) from fresh Solanum tuberosum (cv. Pompadour) material by implementing a new preparation scheme using centrifugal partition chromatography (CPC). A setup for obtaining solanidine by hydrolysis of the glycoalkaloids found in the skin and sprouts of S. tuberosum was first developed. Then its isolation was carried out by the development of CPC conditions: the solvent system used for separation was ethyl acetate/butanol/water in the ratio 42.5:7.5:50 v/v/v, 0.6 g of crude extract were separated with a 8 mL/min flow rate of mobile phase while rotating at 2500 rpm. A run yielded 98 mg of solanidine (86.7 % recovery from the crude extract) in a one‐step separation. The purity of the isolated solanidine was over 98%. Thus, CPC has proven to be the method of choice to get solanidine of very high purity from S. tuberosum biomass in large quantities.